PENGUKURAN KINERJA PDAM DENGAN PENDEKATAN BALANCED SCORECARD (STUDI KASUS PERUSAHAAN DAERAH AIR MINUM TIRTA BENGI KABUPATEN BENER MERIAH) - Fintari, Inda Harisa; Fachrizal, Fachrizal (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
This study aims to look at how the company PDAM Tirta Bengi as Badan Usaha Milik Daerah (BUMD) are enabled to provide services, provision and management of water in the city of Banda Aceh using the Balance Scorecard. The data used are primary data obtained directly from the subject of research in the form of questionnaires and interviews. And secondary data is data documentation provided by the company, such as the company's financial reports, complaint data, and data on the number of customers. From the results of measurements that have been made known that the performance of PDAM Tirta Bengi overall is quite good, it is shown by the value Scorecard resulting from any perspective